Development of a plasmid-based expression system in Clostridium thermocellum and its use to screen heterologous expression of bifunctional alcohol dehydrogenases (adhEs) - Shuen Hon; Anthony A. Lanahan; Liang Tian; Richard J. Giannone; Robert L. Hettich; Daniel G. Olson; Lee R. Lynd (Metabolic Engineering Communications, 2016)
Clostridium thermocellum is a promising candidate for ethanol production from cellulosic biomass, but requires metabolic engineering to improve ethanol yield. A key gene in the ethanol production pathway is the bifunctional aldehyde and alcohol dehydrogenase, adhE. To explore the effects of overexpressing wild-type, mutant, and exogenous adhEs, we developed a new expression plasmid, pDGO144, that exhibited improved transformation efficiency and better gene expression than its predecessor, pDGO-66. This new expression plasmid will allow for many other metabolic engineering and basic research efforts in C. thermocellum. As proof of concept, we used this plasmid to express 12 different adhE genes (both wild type and mutant) from several organisms. Ethanol production varied between clones immediately after transformation, but tended to converge to a single value after several rounds of serial transfer. The previously described mutant C. thermocellum D494G adhE gave the best ethanol production, which is consistent with previously published results. Keywords: Clostridium Thermocellum, Plasmid, adhE, Structural stability, Gene expression